Autophagy Takes Center Stage as a Possible Cancer Hallmark - Alvarez-Meythaler, Jose G.; Garcia-Mayea, Yoelsis; Mir, Cristina; Kondoh, Hiroshi; LLeonart, Matilde E. (Frontiers in Oncology, 2020)
Cancer remains one of the leading causes of death worldwide, despite significant advances in cancer research and improvements in anticancer therapies. One of the major obstacles to curing cancer is the difficulty of achieving the complete annihilation of resistant cancer cells. In fact, the resistance of cancer cells may not only be due to intrinsic factors or factors acquired during the evolution of the tumour but may also be caused by chemotherapeutic treatment failure. Conversely, autophagy is a conserved cellular process in which intracellular components, such as damaged organelles, aggregated or misfolded proteins and macromolecules, are degraded or recycled to maintain cellular homeostasis. Importantly, autophagy is an essential mechanism that plays a key role in tumour initiation and progression. Depending on the cellular context and microenvironmental conditions, autophagy acts as a double-edged sword, playing a role in inducing apoptosis or promoting cell survival. In this review, we propose several scenarios in which autophagy could contribute to cell survival or cell death. Moreover, a special focus on novel promising targets and therapeutic strategies based on autophagic resistant cells is presented.